Christ to COKE : how image becomes icon - Kemp, Martin (Oxford University Press, 2012)
Image, branding, and logos are obsessions of our age. Iconic images dominate the media. Christ to Coke is the first book to look at all the main types of visual icons. It does so via eleven supreme and mega-famous examples, both historical and contemporary, to see how they arose and how they continue to function. Along the way, we encounter the often weird and wonderful ways that they become transformed in an astonishing variety of ways and contexts. How, for example, has the communist revolutionary Che become a romantic hero for middle-class teenagers?The stock image of Christ's face is the fo.